Edukasi Handling Restrain Kucing Kelinci Untuk Meningkatkan Kompetensi Siswa Kesehatan Hewan SMK PP Wiyata Bakti - Yose Iyya Amelia Kurniawan; Fia Amalia; Nofan Rickyawan; Roja Kurnia Noorshy (Penerbit Goodwood, 2026)
Purpose: This community service aimed to improve the knowledge and skills of students from SMK PP Wiyata Bakti Dau in handling and restraining cats (Felis catus) and rabbits (Oryctolagus cuniculus) safely and in accordance with animal welfare principles. Research methodology: The activity was conducted at SMK Pertanian Pembangunan Wiyata Bakti Dau, Malang Regency. Learning methods included a pre-test, theoretical presentation using PowerPoint, posters, and leaflets, live demonstrations, hands-on practice by students, a post-test, and a survey using the Indeks Kepuasan Masyarakat (IKM). Data were analyzed descriptively to determine the percentage increase in knowledge and satisfaction. Results: The average score increased from 68.6% (pre-test) to 97.3% (post-test), showing a 28.7% improvement. The IKM result reached an average score of 89.16%, categorized as “Excellent” (A) according to the Ministry of Administrative and Bureaucratic Reform standards. Students expressed high satisfaction with the balance of theory and practice, and practical sessions were considered essential for reinforcing understanding. Conclusions: The program effectively enhanced students’ understanding and practical skills in animal handling and restraint. It is recommended to continue similar training with additional topics on animal health to further support student readiness for future professional practice. Limitations: The study was limited to a short duration and a small group of students from one school, without long-term evaluation of knowledge or skill retention. Contributions: This study contributes to veterinary education by enhancing students’ skills in safe animal handling and restraint. It serves as a model for similar training in other schools to promote animal welfare and practical learning.